A Scalable DES Based Hashing Algorithm - Bhatti, Shafaan Khaliq; Aamir, Khalid Mahmood; Deriche, Mohamed (International Arab Conference on Information Technology (Online), 2023)
Hash functions are used to transform any size data to a fixed size data. The hash function produces hash values, hash codes, hash sums, or simply hashes. Currently, the SHA family is considered the state-of-the-art hashing algorithm. None of the SHA family algorithms is scalable which is why the SHA family algorithms are not usable for smart devices, especially IoT devices. We propose a DESSHA (DES based Scalable Hashing Algorithm) for smart devices using IoT. DESSHA due to its scalability, provides message authentication for nearly all types of smart devices on IoT, especially for E-Commerce purposes. The analysis will show that DESSHA and SHA algorithms have the same security level for message authentication.